(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This empirical study analyses the implementation and perception of plea bargaining within Maharashtra’s criminal judicial system, focusing on six districts Thane, Pune, Satara, Sangli, Kolhapur and Ratnagiri. Using a mixed-data approach, primary data were collected from 408 stakeholders including advocates, government prosecutors, judges and participating parties through structured questionnaires. Secondary data were drawn from legislative documents, judicial reports, case laws, committee recommendations and government records since the introduction of plea bargaining in 2006. The findings indicate that the majority of respondents consider the plea bargaining mechanism to be effective, with 37.3% rating it “very well” and 35.5% “somewhat.” However, the system remains under-utilized, largely due to low public awareness, limited legal literacy and resistance among defendants to admit guilt. Most respondents strongly supported stricter regulatory guidelines (76.2%), strengthening legal-aid services (78.2%) and the presence of investigating officers during bargaining (73.3%). The study also notes overwhelming support for judicial acceptance of settlement-based compromises (87.3%) and a dedicated authority for plea bargaining matters (89%). The research concludes that while plea bargaining holds promise for reducing pendency and ensuring speedy justice, structural reforms, awareness initiatives and procedural safeguards remain essential for its credible evolution in Maharashtra.